The Feathered Headdress from the Austral Islands at The Royal Museums of Art and History, Brussels: The Conservation of a Masterpiece - Griet Kockelkoren; Hugo DeBlock; Emma Damen; Marina Van Bos (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This contribution mainly focusses on the recent research and conservation of a feathered headdress from the Austral Islands in the collections of The Royal Museums of Art and History in Brussels. It goes into several steps and choices of curation and conservation, and proposes steps for the future of exhibiting such valuable and significant things of cultural heritage and indigenous property.